25 years of N-heterocyclic carbenes: activation of both main-group element–element bonds and NHCs themselves. Issue 14 (17th December 2015) - Würtemberger-Pietsch, Sabrina; Radius, Udo; Marder, Todd B.
Abstract : Expanding the belt! NHC ring expansion reactions and E–E activation from the 1960s till the present are summarized. Abstract : N-Heterocyclic carbenes (NHCs) are widely used ligands and reagents in modern inorganic synthesis as well as in homogeneous catalysis and organocatalysis. However, NHCs are not always innocent bystanders. In the last few years, more and more examples were reported of reactions of NHCs with main-group elements which resulted in modification of the NHC. Many of these reactions lead to ring expansion and the formation of six-membered heterocyclic rings involving insertion of the heteroatom into the C–N bond and migration of hydrides, phenyl groups or boron-containing fragments. Furthermore, a few related NHC rearrangements were observed some decades ago. In this Perspective, we summarise the history of NHC ring expansion reactions from the 1960s till the present.